EFFECTS OF YTTRIA STABILIZED ZIRCNIA (YSZ) COATING ON C.I ENGINE USING CITRONELLA OIL BLEND AS FUEL (International Journal of Food and Nutritional Sciences, 2022)
In addition to the rapid depletion of conventional energy supplies brought on by rising demand, diesel-based fuels are also substantial contributors to air pollution. In modern times, fossil fuels have supplied the bulk of India’s energy needs. Therefore, it is time that alternative fuels for engines be sourced locally. India's rich agricultural landscape provides enough opportunity for processing a variety of oil seeds. Higher power density, better fuel efficiency, and a hotter combustion chamber are just a few of the benefits of ceramic coatings in diesel engines. Increased engine power, lower specific fuel consumption, and higher exhaust gas temperatures are all possible thanks to thermal barrier coating. Although several other systems have served as TBC, yttria-stabilized zirconia has been the focus of the majority of research. Thermal conductivity, chemical stability at the service temperature, strong thermo mechanical stability to the maximum service temperature, and the thermal expansion coefficient all play significant roles in the durability of thermal barrier coatings. Therefore, in the I.C. Engines Laboratory, a four-stroke, single-cylinder, water-cooled Diesel Engine test rig is used to compare the efficiency and emissions of diesel and various citronella oil blends utilizing a yttria-stabilized zirconia-coated piston. The performance of a diesel engine was tested using citronella oil mixes of 10%, 20%, 30%, and 40% by volume. Experimental examination of the engine is used to derive performance characteristics including brake power, specific fuel consumption, and thermal efficiency. Carbon monoxide, carbon dioxide, nitrogen oxide, and unburned hydrocarbon are only some of the emissions that are tracked.